THE APPLICATION OF STANDARD OPERATIONAL PROCEDURES BY FRONT OFFICE DEPARTEMENT TO INCREASE GUESTS’ SATISFACTION IN THE HAVEN BALI SEMINYAK - I Kadek Deo Sudiatmita; I Wayan Jendra; Luh Linna Sagitarini; Lien Darlina (Journal of Applied Sciences in Travel and Hospitality, 2018)
This study aims to find out the application of standard operational procedures by front office departments in The Haven Bali Seminyak to improve guest satisfaction and to know the implementation of SOP (Standard Operation Procedure) that need to be improved and maintained by front office department. There are 15 SOP that are divided into 3 SOP namely GSA, GRO and BSA. Respondents in this research are 10 of the management ranks in the Front Office Department of The Haven Bali Seminyak. This research uses quantitative descriptive analysis technique using Likert scale 5 level. The data obtained were processed using the technique of descriptive statistic. In this study, the entire implementation of standard operational procedures by the department of front office shows that the implementation is fully implemented, although from 15 existing SOP, there are 4 SOP that need to be upgraded: welcome greetings, VIP check-in and check-out guest handling, luggage storage, and baggage arrival. Therefore, the company needs to provide training with the approach and training method by using the standard operational procedure themseves so that the services provided can satisfy the guests.